2021
DOI: 10.1016/j.jbc.2021.100255
|View full text |Cite
|
Sign up to set email alerts
|

A general chemical crosslinking strategy for structural analyses of weakly interacting proteins applied to preTCR–pMHC complexes

Abstract: T lymphocytes discriminate between healthy and infected or cancerous cells via T-cell receptor-mediated recognition of peptides bound and presented by cell-surface-expressed major histocompatibility complex molecules (MHCs). Pre-T-cell receptors (preTCRs) on thymocytes foster development of αβT lymphocytes through their β chain interaction with MHC displaying self-peptides on thymic epithelia. The specific binding of a preTCR with a peptide–MHC complex (pMHC) has been identified previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Recent structural and biophysical data, however, reveal direct interactions between preTCRs and pMHC ligands that utilize a horizontal binding mode compatible with facile mechanosensing 8, 10, 24 . Moreover, functional assays demonstrate both restricted proliferation and repertoire development in the absence of stromal MHCI and MHCII molecules 7, 8 .…”
Section: Figmentioning
confidence: 99%
“…Recent structural and biophysical data, however, reveal direct interactions between preTCRs and pMHC ligands that utilize a horizontal binding mode compatible with facile mechanosensing 8, 10, 24 . Moreover, functional assays demonstrate both restricted proliferation and repertoire development in the absence of stromal MHCI and MHCII molecules 7, 8 .…”
Section: Figmentioning
confidence: 99%
“…It was found that the N30preTCR interacted robustly with the ovalbumin octapeptide SIINFEKL and its Q4H7 derivative SIIQFEHL bound to H‐2K b (Das et al, 2016; Mallis et al, 2019), suggesting that certain ligands of preTCRs could engender greater affinities than observed for the cognate ligands of the αβTCRs. To date, a single preTCR‐pMHC interaction, that of N15preTCR‐VSV8/K b , has been extensively characterized first by NMR‐directed modeling (Mallis et al, 2018) and subsequently by cross‐linking assisted x‐ray crystallography (Li et al, 2021; Mizsei et al, 2021). A road map has been established for the characterization of a larger set of preTCR‐pMHC, which suggests that NMR screening of interactions followed by crosslinking and modeling or crystallography (Mizsei et al, 2021) can establish binding modes of a variety of interactions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a single preTCR‐pMHC interaction, that of N15preTCR‐VSV8/K b , has been extensively characterized first by NMR‐directed modeling (Mallis et al, 2018) and subsequently by cross‐linking assisted x‐ray crystallography (Li et al, 2021; Mizsei et al, 2021). A road map has been established for the characterization of a larger set of preTCR‐pMHC, which suggests that NMR screening of interactions followed by crosslinking and modeling or crystallography (Mizsei et al, 2021) can establish binding modes of a variety of interactions. However, since each β subunit may be derived from one of many TRBV genes, the protein biochemistry, including the folding of the subunit, is sometimes problematic, leading to low refold yields.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to realize the regenerable immunosensor, chemical immobilization of antibodies via chemical cross-linking is required to resist the regeneration processes, as the chemical cross-linking creates a strong bond between the target protein and solid support [ 1 , 19 , 20 ]. Crosslinkers covalently link proteins and impart additional properties according to their reactivity and spacing arm length [ 21 , 22 ]. Because the reactive ends of crosslinkers bind to specific functional groups of the target molecules, crosslinkers have been widely utilized to characterize biomolecule interactions, such as the relationship between adjacent proteins, ligand-receptor interactions, three-dimensional protein structures and molecular association in cell membranes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%